Penulisan Naskah Video Feature “Kopi Manglayang: Nafas Petani dari Lereng Gunung” dengan Menerapkan Struktur Tiga Babak - Saeful Fatah Zaelani; Ryan Krisna Gautama; Encang Saepudin; Rifky Adinur Zein (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The scriptwriter is an important role in the production process of a feature video, particularly in arranging the storyline, building the narrative structure, and directing the delivery of messages so they can be well received by the audience. In the feature video “Kopi Manglayang: Breath of Farmers from the Mountain Slopes”, the scriptwriter plays a role in composing a story about the lives of coffee farmers on the slopes of Mount Manglayang through the application of a three-act structure, namely setup, confrontation, and resolution. The purpose of this final project report is to explain the application of narrative elements in the setup, confrontation, and resolution stages in writing the script for the feature video “Kopi Manglayang: Breath of Farmers from the Mountain Slopes”. The writing method uses a descriptive approach to explain the scriptwriting process systematically, comprehensively, and in detail according to the stages of production. The synthesis of the work in the setup stage presents an introduction to the atmosphere of Mount Manglayang’s slopes, the activities of coffee farmers, and the social conditions that form the basis of the story. In the confrontation stage, the writer presents various challenges and struggles faced by the farmers in maintaining coffee quality amid environmental and economic conditions. In the resolution stage, the story concludes with messages of hope, the spirit of preserving local coffee, and the meaning of the farmers’ struggles as the main message of the work. In conclusion, the application of narrative elements in the three-act structure helps the scriptwriter create a feature video storyline that is well-structured, informative, and emotionally engaging for the audience.